Social system of production in Germany - a model for future? - Michal Moszynski (Institute of Economic Research (IER), 2015)
The concept of a social system of production (SSP) is one of the cognitive perspectives by which the institutional arrangements of modern market economies could be analysed. It allows reflections on the autonomy of institutional arrangements in each country, in line with the assumption put by the Variety of Capitalism approach, as well as to investigate problems of stability of the given institutional configuration and the complementarity of their components. The following study raises these issues on theoretical basis and carries out their preliminary verification on the example of German SSP, with special regard to the labour market. Basing on the critical study of literature a set of specific features of the German model is proposed, structured according to the concept of SSP in four main categories: institutions, organizations, social values and economic policy. Then, using a secondary statistical data and qualitative analysis, some trends has been identified occurring within these elements in order to verify the thesis of complementarity and the stability of the German social production system.
Keywords: J40; J52; L16; L23; P17; 330; Germany; labour market; institutions; social system of production